Design of a performance assessment instrument for blind employees of a social enterprise - Macías Quezada, Jesús José (2011)
Dialogue Social Enterprise (DSE), an expanding German franchising social business, requires to maintain quality in the performance of its tour guides worldwide for its branch Dialogue in the Dark (DiD). DiD offers exhibitions and other products in the “dark” around the world. Additionally, DSE wants to develop human resources tools to offer to its licensees. Thus, DSE proposes a first phase of research and design of an action plan. A second testing phase can be offered if the action plan can go beyond licensees policies constrains. Considering that the position of tour guide is unique since it is performed exclusively by visually impaired people, based on theoretical research and on DSE data gathering and analysis, and supported by a DSE panel of experts, this research proposes a design of a blind tour guides’ performance multisource assessment instrument through the action research method.